Advance and Retreat of Cordilleran Ice Sheets in Washington, U.S.A. - Easterbrook, Don (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1992)
ABSTRACTCordilleran Ice Sheet glaciations show characteristic patterns of advance and retreat, consisting of (1) advance out outwash, (2) glacial scouring, (3) deposition of till, (4) deposition of recessional outwash south of Seattle in the southern Puget Lowland, glaciomarine drift in the northern lowland, and eskers, kames, and small moraines on the Columbia Plateau. Radiocarbon dates show that the Puget and Juan de Fuca lobes advanced and retreated synchronously. The Puget lobe backwasted to Seattle by 13.4-14 ka yrs BP, where the thinning ice floated in seawater northward to Canada by 13 ka yrs BP depositing glaciomarine drift contemporaneously over 18,000 km2. Compelling evidence against the backwasting, calving, terminus model for the origin of the glaciomarine drift includes: 1) abundant 14C dates demonstrate simultaneous deposition of glaciomarine drift over the entire area; 2) stagnant-ice deposits closely related to glaciomarine drift are not consistent with an actively-calving, backwasting terminus; 3) irrefutable evidence for the nonmarine origin of Deming sand shows that Cordilleran ice was absent immediately prior to deposition of the overlying glaciomarine drift. The pattern of events in the northern Puget Lowland includes: 1) glacial loading under 1800 m of ice during the Vashon maximum; 2) rapid glacial thinning and floating of the ice deposited Kulshan glaciomarine drift 12-13 ka yrs BP; 3) emergence and deposition of fluvial Deming sand 11.5 ka yrs BP; 4) resubmer-gence and deposition of Bellingham glaciomarine drift up to -200 m, well beyond global eustatic sea level rise; 5) emergence 10.5-11.5 ka yrs BP and deposition of Sumas outwash on Bellingham glaciomarine drift; 6) Holocene eustatic sea level rise kept pace with isostatic rebound, thus, post-Sumas marine terraces are absent.